Environmental Health and Societal Wealth Predict Movement Patterns of an Urban Carnivore - Christine E. Wilkinson; Niamh Quinn; Curtis Eng; Christopher J. Schell (Ecology Letters, 2025)
How societal, ecological and infrastructural attributes interact to influence wildlife movement is uncertain. We explored whether neighbourhood socioeconomic status and environmental quality were associated with coyote ( Canis latrans ) movement patterns in Los Angeles, California and assessed the performance of integrated social–ecological movement models. We found that coyotes living in more anthropogenically burdened regions (i.e. higher pollution, denser development, etc.) had larger home ranges and showed greater daily displacement and mean step length than coyotes in less burdened regions. Coyotes experiencing differing levels of anthropogenic burdens demonstrated divergent selection for vegetation, pollution, road densities and other habitat conditions. Further, movement models that included societal covariates performed better than models that only assessed ecological features and linear infrastructure. This study provides a unique social–ecological lens examining the anthropogenic drivers of urban wildlife movement, which should be applicable to urban planners and conservationists when building more equitable, healthy and wildlife‐friendly cities.

Hydroxylated polymethoxyflavones reduce the activity of pancreatic lipase, inhibit adipogenesis and enhance lipolysis in 3T3-L1 mouse embryonic fibroblast cells - Bilal Ahmad; Emily P. Friar; Muhammad Sufyan Vohra; Nasar Khan; Christopher J. Serpell; Michelle D. Garrett; Jason Siau Ee Loo; Isabel Lim Fong; Eng Hwa Wong (Chemico-Biological Interactions, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Overview of Urethral Reconstruction by Tissue Engineering: Current Strategies, Clinical Status and Future Direction - Zahra Rashidbenam; Mohd Hafidzul Jasman; Pezhman Hafez; Guan Hee Tan; Eng Hong Goh; Xeng Inn Fam; Christopher Chee Kong Ho; Zulkifli Md Zainuddin; Reynu Rajan; Fatimah Mohd Nor; Mohamad Aznan Shuhaili; Nik Ritza Kosai; et al. (Tissue Engineering and Regenerative Medicine, 2019)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Synchrotron micro-scale study of trace metal transport and distribution in Spartina alterniflora root system in Yangtze River intertidal zone - Huan Feng; Weiguo Zhang; Wenliang Liu; Lizhong Yu; Yu Qian; Jun Wang; Jia-Jun Wang; Christopher Eng; Chang-Jun Liu; Keith W. Jones; Ryan Tappero (Environmental Science and Pollution Research, 2015)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Reconstituted human oral and esophageal mucosa in culture - Dolphine Oda; Christopher E. Savard; Lydia Eng; John Sekijima; Geoffrey Haigh; Sum P. Lee (In Vitro Cellular & Developmental Biology - Animal, 1998)